2019
DOI: 10.13110/humanbiology.91.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of 10 X-STR Markers in Populations of Northeast Argentina

Abstract: In northeast Argentina, different Amerindian communities share territory and history with settlers, mainly Europeans. Due to miscegenation, the current Argentinian population has a particular structure that can be described through the X chromosome variation. Our objectives are: to describe the variation of 10 X-STRs in urban populations of the Argentinian regions known as Gran Chaco and Mesopotamia; to report the forensic parameters of these STRs, and to estimate the European and indigenous genetic components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Genetic differences have also been found among different regions or provinces within Argentina, for several genetic polymorphisms, whether they were coding or non-coding markers (Corach et al, 2006;Di Santo Meztler et al, 2018;Muzzio et al, 2018;Sala et al, 2018;Caputo et al, 2021, among others). Interestingly, some differences emerged even when comparing Resistencia and MNP, which are located in the same province and only 425 km apart, as it was previously reported for non-coding markers (Di Santo Meztler et al, 2019). Our results showed less genetic differentiation among Argentinian populations, probably because the polymorphisms here analyzed are located in coding regions, having less chances for displaying variability.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Genetic differences have also been found among different regions or provinces within Argentina, for several genetic polymorphisms, whether they were coding or non-coding markers (Corach et al, 2006;Di Santo Meztler et al, 2018;Muzzio et al, 2018;Sala et al, 2018;Caputo et al, 2021, among others). Interestingly, some differences emerged even when comparing Resistencia and MNP, which are located in the same province and only 425 km apart, as it was previously reported for non-coding markers (Di Santo Meztler et al, 2019). Our results showed less genetic differentiation among Argentinian populations, probably because the polymorphisms here analyzed are located in coding regions, having less chances for displaying variability.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have shown genetic differences between these four populations using non coding X chromosome markers (SNPs, INDELs and STRs) (Di Santo Meztler, 2018;Di Santo Meztler et al, 2019). Also, differences between a native Wichí community of Chaco and the population of Resistencia were found in the OPRK1 gene (Raggio et al, 2018).…”
Section: Historical Eventsmentioning
confidence: 94%
“…Along with Alu repeats, the potential of X chromosomal haploblocks still to be explored by studying different population samples from different geographical regions to establish their credibility. While analyzing the difference at genetic level North-East Argentina Populations, (DI SANTO MEZTLER et al, 2019) the Found the usefulness of Alu repeats for the comparison of distantly related population samples.…”
Section: Other X Chromosomal Markersmentioning
confidence: 99%